DESKRIPSI KETERAMPILAN MENULIS LAPORAN PRAKTIKUM KIMIA ANALITIK II MAHASISWA PENDIDIKAN KIMIA FKIP UNTAN - Noviana, Rut; Hairida, Hairida; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research intend to describe the abilities of TanjungpuraUniversity Chemistry Education Students in writing AnalyticalChemistry II practicum reports. This research involved 15 students ofChemistry Education FKIP Tanjungpura University for the 2018/2019academic year. The form of the research is descriptive research usingthe case study method. The research instrument used was first testedfor its validity using the Gregory content validation technique with ahigh validity at 0.8. The research instrument is a skills assessmentrubric with five assessment aspects, wich is skills in writing reporttitles, suitability of report content with the object of observation, reportoutline, report discussion and spelling accuracy. The data analysistechnique was carried out by giving a score to the scoring rubric basedon the criteria in the scoring rubric, adding up the scores of all aspectsobserved and then converting the score into a percentage value. Theresults of data analysis showed that the ability of students of ChemistryEducation FKIP Tanjungpura University in writing AnalyticalChemistry II practicum reports was classified as skilled with anaverage of 87.7%.